The sociology of groups and the economics of incentives: theory and evidence on compensation systems - William E. Encinosa; Martin Gaynor; James B. Rebitzer (Institute for the Study of Labor (IZA), 2005)
When working together, people engage in non-contractual and informal interactions that constitute the sociology of the group. We use behavioral models and a unique survey of medical groups to analyze how group sociology influences physician incentive pay and behavior. We conclude that informal interactions among group members influence pay practices and behaviors, but the relationship is complex. No single aspect of group sociology is entirely consistent with all the patterns in the data. Factors emphasized in the economic theory of agency, notably risk aversion, also shape pay policies but these factors cannot account for all the observed empirical relationships.
Keywords: D21; D22; J40; J41; 330; incentives; social norms; physicians; Vergütungssystem; Leistungsorientierte Vergütung; Leistungsanreiz; Soziale Norm; Soziale Gruppe; Ärzte; Theorie